Range of sensory gating values and test-retest reliability in normal subjects - Fuerst, Darren R.; Gallinat, Jürgen; Boutros, Nash N. (Psychophysiology, 2007)
This article characterizes gating in normal subjects using P50, N100, and P200 components in a paired‐click paradigm and compares the test–retest reliabilities of the three components. Sixty‐seven normal subjects had gating data from a standard paired‐click paradigm; 30 had test–retest data. The test–retest reliability of the amplitudes, latencies, and sensory gating indices derived from the P50, N100, and P200 responses were compared. Measured gating ratios showed either normal or positively skewed distributions. Test–retest reliability of the P50 gating ratio did not reach significance, but N100 and P200 ratios showed better reliability (.50 and .64). The P50 difference score was more reliable (.61), and the N100 and P200 test–retest reliabilities of difference scores were high (.83 and .81, respectively). N100 and P200 attenuation is reliable; further work is needed to develop more reliable P50 gating measures.